Speech Acts in Katarina Blom’s TEDx Talks: A Pragmatic Study - Karwur, Alvenia Ester; Ismail, Ismail; Paendong, Stevean Misael (PRASASTI: Journal of Linguistics, 2026)
This study analyzed speech acts in Katarina Blom’s TEDx Talk “You Don’t Find Happiness, You Create It,” using Searle’s (1979) Speech Act Theory. Few studies explore speech acts in motivational public discourse, despite their persuasive impact. The research aimed to identify and categorize speech acts in the talk’s transcript, employing a qualitative descriptive method with content analysis. Findings revealed assertive speech acts dominated (80.1%), conveying facts and personal insights, followed by directives (19.9%), encouraging audience reflection, and minimal expressive acts (2.1%), fostering emotional connection. No commissive or declarative acts were found, reflecting the talk’s focus on inspiration over commitment. This study extends speech act theory to motivational speeches, offering insights for public speakers to enhance communication effectiveness.